2008
DOI: 10.1007/s00213-008-1134-7
|View full text |Cite
|
Sign up to set email alerts
|

Alprazolam potentiates the antiaversive effect induced by the activation of 5-HT1A and 5-HT2A receptors in the rat dorsal periaqueductal gray

Abstract: Alprazolam as antidepressants compounds facilitates 5-HT(1A)- and 5-HT(2A)-receptor-mediated neurotransmission in the DPAG, implicating this effect in the mode of action of different classes of antipanic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 58 publications
(88 reference statements)
1
11
0
2
Order By: Relevance
“…imipramine, sertraline, alprazolam) may also affect 5-HT 1A -mediated signalling within the DPAG by a different mechanism : by enhancing the responsiveness of these receptors (de Bortoli et al 2006(de Bortoli et al , 2008Jacob et al 2002 ;Mongeau & Marsden, 1997 ;Zanoveli et al 2005Zanoveli et al , 2007. For instance, in DPAG, doses of o1.6 nmol 8-OH-DPAT, a 5-HT 1A receptor agonist, are required to inhibit escape performance in the elevated T-maze (de Paula Soares & Zangrossi, 2004 ;Zanoveli et al 2003Zanoveli et al , 2005.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…imipramine, sertraline, alprazolam) may also affect 5-HT 1A -mediated signalling within the DPAG by a different mechanism : by enhancing the responsiveness of these receptors (de Bortoli et al 2006(de Bortoli et al , 2008Jacob et al 2002 ;Mongeau & Marsden, 1997 ;Zanoveli et al 2005Zanoveli et al , 2007. For instance, in DPAG, doses of o1.6 nmol 8-OH-DPAT, a 5-HT 1A receptor agonist, are required to inhibit escape performance in the elevated T-maze (de Paula Soares & Zangrossi, 2004 ;Zanoveli et al 2003Zanoveli et al , 2005.…”
Section: Discussionmentioning
confidence: 96%
“…More recently, it has been reported that long-, but not short-term, administration of the clinically effective anti-panic drugs imipramine (Jacob et al 2002 ;Mongeau & Marsden, 1997), fluoxetine (de Bortoli et al 2006), sertraline (Zanoveli et al 2007) and alprazolam (de Bortoli et al 2008) facilitate the inhibitory effect on escape caused by intra-DPAG injections of 5-HT 1A and 5-HT 2A receptor agonists. This effect was not observed after long-term treatment with buspirone (de Bortoli et al 2006 ;Zanoveli et al 2005), a partial 5-HT 1A receptor agonist with clinically relevant anxiolytic properties, but ineffective in panic disorder (Connor & Davidson, 1998 ;den Boer & Slaap, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Curiously, in the dPAG, chronic treatment with clinically effective antipanic drugs such as imipramine, fluoxetine, and alprazolam causes the opposite effect on 5-HT2A receptors, i.e. these drugs enhance the anti-escape effect caused by local injection of DOI, indicating that these receptors were sensitized (de Bortoli et al 2006(de Bortoli et al , 2008. Results such as these are indicative that the signaling pathway involving 5-HT2A receptors/GABA neurotransmission in the dPAG may play a distinctive role in different aspects of panic disorder.…”
Section: Discussionmentioning
confidence: 98%
“…followed by local anesthesia (2% lidocaine with a vasoconstrictor; Harvey, Brazil) and placed in a stereotaxic frame (David Kopf, USA) for implantation of a chemitrode in the dPAG as previously described by de Bortoli et al (2008). The chemitrode was made of a stainless-steel guide cannula (outside diameter 0.6 mm, 13 mm long) glued to a brain electrode made of stainless-steel wire (diameter 250 mm), enamel-insulated, except at the cross-section of the tip, reaching 1 mm below the lower end of the cannula.…”
Section: Surgerymentioning
confidence: 99%
“…The anti-panic effects appear to be mediated by 5-HT 1A and 5-HT 2A receptors as intra-DPAG microinjections of antagonists at these receptors block the effects of DR stimulation on escape (Pobbe and Zangrossi, Jr., 2005). Intra-DPAG injections of 5-HT 1A and 5-HT 2A receptor agonists (de Bortoli et al, 2008;de Bortoli et al, 2006;Jacob et al, 2002;Zanoveli et al, 2005;Zanoveli et al, 2007), but not 5-HT 2C receptor agonists (Yamashita et al, 2011), inhibit escape behaviors, either following electrical stimulation of the DPAG, or as assessed in intact, unstimulated, rats exposed to the elevated T-maze. Intra-DPAG injections of 5-HT 1A and 5-HT 2A receptor antagonists in the absence of electrical stimulation of the DPAG have no effect on escape behaviors (de Paula Soares and Zangrossi, Jr., 2004;Nogueira and Graeff, 1995;Yamashita et al, 2011;Zanoveli et al, 2010), suggesting that there is little or no tonic serotonergic influence on DPAG-mediated escape behaviors.…”
Section: A Putative Panic Inhibition System Involving the Amygdalamentioning
confidence: 99%